2002
DOI: 10.1038/sj.leu.2402688
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated donor umbilical cord blood transplantation in adults

Abstract: Umbilical cord blood (UCB) has emerged as an appealing alternative source of hematopoietic stem cells for unrelated donor transplantation. Shorter time to transplant and an improved chance of finding a suitable graft are evident advantages over bone marrow transplantation from unrelated donors. The majority of UCB transplants from unrelated donors have been performed in children, but the number in adults has been growing steadily in recent years. We review herein the reported experience with that source of hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
2
25
1
1
Order By: Relevance
“…10 In our study cohort, the Kaplan-Meier estimate of neutrophil engraftment was 89% overall, which is similar to that reported in other studies. 1,2,10,14,20,34 Similar to Wagner et al, 10 our results also showed the importance of the CD34 cell dose; UCB recipients who received a higher infused CD34 cell dose (X1.7 Â 10 5 /kg) had a higher probability of engraftment. In addition, the time to neutrophil engraftment was significantly quicker with a higher infused CD34 cell dose.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…10 In our study cohort, the Kaplan-Meier estimate of neutrophil engraftment was 89% overall, which is similar to that reported in other studies. 1,2,10,14,20,34 Similar to Wagner et al, 10 our results also showed the importance of the CD34 cell dose; UCB recipients who received a higher infused CD34 cell dose (X1.7 Â 10 5 /kg) had a higher probability of engraftment. In addition, the time to neutrophil engraftment was significantly quicker with a higher infused CD34 cell dose.…”
Section: Discussionsupporting
confidence: 76%
“…The duration of neutropenia was reduced by a median of 8 days in recipients of cord units with a higher CD34 cell count. In contrast to other Unrelated cord blood transplant in Australia and New Zealand TE Petterson et al studies, however, 2,4,6,14,16,17 we found no impact on the probability or speed of neutrophil engraftment with larger infused TNC doses. Similarly, there was no impact of HLA disparity, diagnosis or conditioning regimen on neutrophil engraftment.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations